The Bidar Boat Festival as a Heritage Sporting Event: A Sustainability Perspective - Az Zahrah Lumongga; Setiawan; Yustikasari; Kevin Muhamad Lukman (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
This study examines the Bidar Boat Festival in Palembang as a Heritage Sporting Event (HSE) from a sustainability perspective. The study aims to analyze how the festival contributes to cultural preservation, social participation, local economic development, environmental sustainability, and institutional governance within the context of sustainable sport tourism. This research employed a qualitative case study design using semi-structured interviews, field observations, and document analysis involving government institutions, event organizers, rowing participants, local communities, visitors, and MSME actors. The findings reveal that the festival demonstrates strong cultural and social sustainability through the preservation of traditional rowing practices, community participation, intergenerational cultural transmission, and the reinforcement of river-based identity. Economically, the festival contributes to tourism activities and local economic circulation, although the benefits remain unevenly distributed among stakeholders. Environmental sustainability remains relatively weak due to reactive waste management, limited ecological awareness, and dependence on fossil-fuel-based river transportation. Institutional sustainability is also constrained by fragmented governance and limited cross-sectoral coordination. The study concludes that the long-term sustainability of heritage sporting events requires integrated governance, environmental management, equitable economic support, and the preservation of cultural authenticity to balance tourism development and community sustainability.